2019
DOI: 10.1158/1055-9965.epi-18-0570
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value and Regulatory Mechanisms of microRNA-145 in Various Tumors: A Systematic Review and Meta-analysis of 50 Studies

Abstract: Acting as an important tumor-related miRNA, the clinical significance and underlying mechanisms of miR-145 in various malignant tumors have been investigated by numerous studies. This study aimed to comprehensively estimate the prognostic value and systematically illustrate the regulatory mechanisms of miR-145 based on all eligible literature.Relevant studies were acquired from multiple online databases. Overall survival (OS) and progression-free survival (PFS) were used as primary endpoints. Detailed subgroup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 114 publications
0
16
0
Order By: Relevance
“…In colon and breast cancer cells, miR-145 reduces the levels of several oncoproteins, such as c-MYC and VEGF [ 35 , 36 ], decreasing cell proliferation and the angiogenic potential of cancer cells. In EOC, miR-145 was proposed as a diagnosis marker and predictor of disease outcome [ 37 , 38 ]. In addition, recent evidence shows that downregulation of miR-145 levels in EOC samples induces an increase in several oncoproteins and thus, promotes EOC progression [ 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…In colon and breast cancer cells, miR-145 reduces the levels of several oncoproteins, such as c-MYC and VEGF [ 35 , 36 ], decreasing cell proliferation and the angiogenic potential of cancer cells. In EOC, miR-145 was proposed as a diagnosis marker and predictor of disease outcome [ 37 , 38 ]. In addition, recent evidence shows that downregulation of miR-145 levels in EOC samples induces an increase in several oncoproteins and thus, promotes EOC progression [ 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-145, located in a fragile region of chromosome 5q has been reported to play a tumor suppressor role in a variety of other cancers, including NB [19]. As a cancer suppressor gene, it inhibits proliferation, invasion, and metastasis of tumor cells, increases sensitivity to chemotherapeutic drugs, and regulates the development and progression of tumors [20,21]. Decreased miR-145 expression has reported in a wide range of tumors including prostate, bladder, colon, ovarian, and esophageal cancers, suggesting a potential role in disease pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased miR-145 expression has reported in a wide range of tumors including prostate, bladder, colon, ovarian, and esophageal cancers, suggesting a potential role in disease pathology. In-depth studies suggest that miR-145 could be an ideal marker for diagnostic and prognostic evaluations of tumors, and that it may also represent a novel target for cancer treatment [21,22]. However, the role of miR-145 in NB is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-145 is a newly discovered miR with signi cantly downregulated expression in breast cancer, cervical cancer, glioma, colon cancer, esophageal cancer, and nonsmall cell lung cancer [25,26]. Many recent studies have found that microRNA is closely related to ovarian cancer [27,28].…”
Section: Discussionmentioning
confidence: 99%